2011
DOI: 10.3109/14767058.2011.556205
|View full text |Cite
|
Sign up to set email alerts
|

Fetal cerebral ventricle volumetry: comparison between 3D ultrasound and magnetic resonance imaging in fetuses with ventriculomegaly

Abstract: Three-dimensional volumetry of fetal LVs by VOCAL method has good agreement with fetal MRI in fetuses with ventriculomegaly and may be used as an additional tool in patient counseling and prognosis prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…When VM is suspected at any stage of pregnancy, a detailed MRI is considered because of the association with poor outcomes, since it can show abnormalities that are not diagnosed with ultrasound . The main advantages of MRI are no shadows, good soft‐tissue contrast, and high resolution, particularly in the third trimester of gestation . Plus, with 3D imaging one may get close to isovoxel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When VM is suspected at any stage of pregnancy, a detailed MRI is considered because of the association with poor outcomes, since it can show abnormalities that are not diagnosed with ultrasound . The main advantages of MRI are no shadows, good soft‐tissue contrast, and high resolution, particularly in the third trimester of gestation . Plus, with 3D imaging one may get close to isovoxel.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fetuses with isolated VM have significantly increased cortical gray matter volumes and the atrial diameter may not be as sensitive to volumetric differences . Therefore, measurement of lateral ventricular volumes may provide suitable further evaluation . Current methods of assessing the volume include manual multisection planimetric (MSP) volume analysis, which manually traces free‐form regions‐of‐interest (ROIs) slice by slice, and 3D reconstructed volumetric datasets analysis .…”
mentioning
confidence: 99%
“…Unilateral ventriculomegaly remains a poorly understood condition, but as suggested elsewhere, this lack of understanding may be due to the difficulties in visualizing both ventricles prenatally 4 . The developing use of 3‐dimensional obstetric sonography will no doubt improve the diagnosis of ventriculomegaly by not only providing more information about the ventricle size and shape but also identifying the cause of the dilatation 21 …”
Section: Discussionmentioning
confidence: 99%
“…By comparing measurements performed by 3-DUS VOCAL with those obtained by magnetic resonance imaging (MRI), Haratz et al (2011) found that 3-DUS volumetry of fetal LV by the VOCAL method correlates well with fetal MRI in fetuses with ventriculomegaly, and that this approach may be used as additional tool in patient counseling and prognosis prediction. VOCAL is a computer program installed on some commercial ultrasound machines that is used for volume calculation and employs poles demarcated with calipers.…”
Section: -D Ultrasound and The Study Of Fetal Brain Anatomy: ''The Nmentioning
confidence: 93%
“…Brazilian researchers (Haratz et al 2011) have evaluated the feasibility of fetal lateral ventricle (LV) volumetry in 30 fetuses at 20 to 36 wk of gestation, with ventricular width ranging from 10 to 30 mm. By comparing measurements performed by 3-DUS VOCAL with those obtained by magnetic resonance imaging (MRI), Haratz et al (2011) found that 3-DUS volumetry of fetal LV by the VOCAL method correlates well with fetal MRI in fetuses with ventriculomegaly, and that this approach may be used as additional tool in patient counseling and prognosis prediction.…”
Section: -D Ultrasound and The Study Of Fetal Brain Anatomy: ''The Nmentioning
confidence: 99%